2017
DOI: 10.1111/1471-0307.12474
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus and Paenibacillus species associated with extended shelf life milk during processing and storage

Abstract: Characterisation of spore formers associated with extended shelf life milk was performed by analysing the bacteriological quality of milk samples collected at various processing stages and during storage. Isolates were identified with MALDI‐TOF‐MS. Milk had spore counts <2 log10 cfu/mL and 4 log10 cfu/mL during processing and storage, respectively. Bacillus pumilus dominated the bacterial population. Bacterial species were inoculated into sterile milk for a shelf life study, and the population change was obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Despite advancement in preservation and processing technologies, Bacillus cereus remains a shelf-life and consumer safety challenge for the dairy industry (Ranieri et al, 2012;Aouadhi et al, 2014;Mugadza and Buys, 2017a). Bacillus cereus is a ubiquitous sporeforming bacterium (Ranieri et al, 2012;Aouadhi et al, 2014) that is reported to produce various toxins responsible for diarrheal and emetic food poisoning (Hansen and Hendriksen, 2001;Bartoszewicz et al, 2008;Stenfors Arnesen et al, 2008).…”
Section: Short Communicationmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite advancement in preservation and processing technologies, Bacillus cereus remains a shelf-life and consumer safety challenge for the dairy industry (Ranieri et al, 2012;Aouadhi et al, 2014;Mugadza and Buys, 2017a). Bacillus cereus is a ubiquitous sporeforming bacterium (Ranieri et al, 2012;Aouadhi et al, 2014) that is reported to produce various toxins responsible for diarrheal and emetic food poisoning (Hansen and Hendriksen, 2001;Bartoszewicz et al, 2008;Stenfors Arnesen et al, 2008).…”
Section: Short Communicationmentioning
confidence: 99%
“…Bacillus cereus is a ubiquitous sporeforming bacterium (Ranieri et al, 2012;Aouadhi et al, 2014) that is reported to produce various toxins responsible for diarrheal and emetic food poisoning (Hansen and Hendriksen, 2001;Bartoszewicz et al, 2008;Stenfors Arnesen et al, 2008). Studies conducted at an extended shelf-life (ESL) milk processing plant revealed the presence of psychrotrophic B. cereus in milk during processing as well as during storage and in filler nozzles after cleaning in place (CIP; Khoza, 2016;Mugadza and Buys, 2017a). A follow-up study on these B. cereus strains then showed close relatedness between these strains using repetitive element palindromic (rep) and 16S partial sequencing (Mugadza and Buys, 2017b).…”
Section: Short Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Extended shelf-life (ESL) milk has the inherent characteristic of a shelf-life longer than that of HTST milk, and lacks the burnt flavor commonly associated with UHT milk (Mugadza and Buys, 2018). A temperature regimen that bridges the gap between HTST and UHT processing is employed in the processing of ESL milk (Lorenzen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of bactofugation and microfiltration significantly reducing spore formers in ESL milk, an increased amount of spore formers in the final product may indicate post‐processing contamination most likely from filler nozzles (Eneroth et al . 2001; Mugadza and Buys, 2018). This could be problematic as we showed in the viability assay that B. cereus spores survived simulated CIP treatment and had the potential of growing under refrigerated conditions over a prolonged period, that is at least 28 days.…”
Section: Discussionmentioning
confidence: 99%